Beyond Customer-based Innovation Adoption : A Further Research on China Market - Shi, Li (2013)
Customer-based innovation adoption based on the customers’ perceptions from organization’s perspective is not as reliable as it is supposed to be. Innovation adoption process involves both organizations and customers. Organizational innovation adoption process is more complicated that companies need to look further into both internal and external factors that impact on the innovation adoption, therefore, build up the most appropriate marketing strategy to distribute their innovation. This is because customer-based innovation adoption cannot only be influenced by their own level of innovativeness, but also depends on the diffusion of innovation, which relies on the communication channels. Therefore, in this paper, a depth discussion will be related to organizational innovation adoption, the factors that influence on the process and innovative marketing strategies that help with SMEs about their innovation diffusion in FMCG industry in China.